2019
DOI: 10.1021/acs.jced.9b00700
|View full text |Cite
|
Sign up to set email alerts
|

Solid–Liquid Equilibrium of Quinary Aqueous Solution Composed of Lithium, Potassium, Rubidium, Magnesium, and Borate at 323.15 K

Abstract: To understand the thermodynamic behaviors of the borate-containing system, the solid−liquid equilibrium data (solubilities, density, and refractive index) of quinary aqueous solution composed of lithium, potassium, rubidium, magnesium, and borate at 323.15 K were determined by using the isothermal dissolution method. The crystalloid forms of the solid phase were confirmed by the X-ray diffraction method. Results show that four single salts Li 2 B 4 O 7 •3H 2 O, K 2 B 4 O 7 •4H 2 O, RbB 5 O 8 • 4H 2 O, and MgB … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…The sevencomponent system Li + , Na + , K + , Rb + , Mg 2+ // Cl − , and borate−H 2 O can be used to describe the composition in the Pingluo underground brine. Until now, some phase equilibria of subsystems related to the above mentioned complex system have been done: ternary systems, such as Li + // Cl − , BO 20,21 The results show that the crystalline form of boron is related to the coexisting ions and temperature. Boron appears in many polymeric forms such as BO − in the solution containing borate.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The sevencomponent system Li + , Na + , K + , Rb + , Mg 2+ // Cl − , and borate−H 2 O can be used to describe the composition in the Pingluo underground brine. Until now, some phase equilibria of subsystems related to the above mentioned complex system have been done: ternary systems, such as Li + // Cl − , BO 20,21 The results show that the crystalline form of boron is related to the coexisting ions and temperature. Boron appears in many polymeric forms such as BO − in the solution containing borate.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The seven-component system Li + , Na + , K + , Rb + , Mg 2+ // Cl – , and borate–H 2 O can be used to describe the composition in the Pingluo underground brine. Until now, some phase equilibria of subsystems related to the above mentioned complex system have been done: ternary systems, such as Li + // Cl – , BO 2 – –H 2 O at 288.2–323.2 K, , Li + , K + // borate–H 2 O and Li + , Rb + // borate–H 2 O at 323.2 K, K + , Rb + // borate–H 2 O and Rb + , Mg 2+ // borate–H 2 O at 323.2 K, Mg 2+ // Cl – , B 6 O 10 2– –H 2 O at 288.2 and 308.2 K, , and Mg 2+ // Cl – , B 4 O 7 2– –H 2 O at 273.2 K; quaternary systems, such as Li + , Na + , Mg 2+ // B 4 O 7 2– –H 2 O at 273.2 K, Li + , K + , Mg 2+ // borate–H 2 O at 348.2 K, Li + , Rb + , Mg 2+ // borate–H 2 O at 298.2–348.2 K, Na + , Mg 2+ // Cl – , B 4 O 7 2– –H 2 O at 273.2 K, Rb + , Mg 2+ // Cl – , borate–H 2 O at 323.2 and 348.2 K; , and quinary system such as Li + , K + , Rb + , Mg 2+ // borate–H 2 O at 323.2 and 348.2 K. , The results show that the crystalline form of boron is related to the coexisting ions and temperature. Boron appears in many polymeric forms such as BO 2 – , B­(OH) 4 – , B 3 O 3 (OH) 4 – , B 4 O 5 (OH) 4 2– , and B 5 O 6 (OH) 4 – in the solution containing borate.…”
Section: Introductionmentioning
confidence: 99%
“…The research results can be used to explore the chemical production process and guide the formulation of the comprehensive utilization process of salt lake brine resources. 13 Up to now, a lot of work have been carried out on phase equilibrium for different types of salt lakes, for example, K + , Rb + // Cl − − H 2 O at 298.15 K; 14 Na + , Mg 2+ , NH 4 + // Cl − − H 2 O at 348.15 K; 15 Na + , Rb + // Cl − − H 2 O at 288.15, 298.2, and 308.15 K; 16 Na + , Rb + , Mg 2+ //Cl − − H 2 O at 298.2 K; 17 Li + , Rb + , Mg 2+ //borate − H 2 O at T = 323 K; 18 Rb + (Mg 2+ )//Cl − , and borate − H 2 O at 323 K; 19 and Li + , K + , Rb + , Mg 2+ // borate − H 2 O, 20 K + , Rb + , Cs + //SO 4 2− − H 2 O at 298.2 K 21 have been used to comprehensively utilize the salt lake. According to the reported sulfate-containing literature, for the quaternary systems Li + , Na + , Cs + //SO 4 2− − H 2 O at 298.2 K; 22 Li + , Na + , Mg 2+ // SO 4 2− − H 2 O at 323 K, 23 and Li + , Cs + , Mg 2+ // SO 4 2− − H 2 O at 298.2 K, 24 it was found that lithium sulfate is difficult to be extracted directly from brine in its single salt form by isothermal crystallization.…”
Section: Introductionmentioning
confidence: 99%
“…Given the rapid development of portable electronic products and new-energy vehicles, the price of, and demand for, lithium resources have increased sharply in recent years (Xu et al, 2020). According to a United States Geological Survey (USGS) report, 62% of lithium resources in the world are present in brine in salt lakes (Yu et al, 2019). Therefore, it is of economic and strategic significance to extract lithium resources from the brine in salt lakes.…”
Section: Introductionmentioning
confidence: 99%